The republics - Handal, Nathalie, 1969- (Pitt poetry series., 2015)
"The Republics is a massively brilliant new work, a leap in literature we have not seen. It's gripping, harrowing, and at times horrific while its form paradoxically is fresh, luscious, and original. Bypassing pity and transforming pain into language Handal stars. She has recorded like Alice Walker, Paul Celan, John Hershey, and Carolyn Forché some of the worst civilization has offered humankind and somehow made it art."-Sapphire